2012
DOI: 10.1097/ccm.0b013e318236f64f
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnoses and autopsy findings

Abstract: This study found significant discrepancies in 18.5% of patients who underwent autopsy, 7.5% of them were diagnoses with impact on therapy and outcome. This reinforces the importance of the postmortem examination in confirming diagnostic accuracy and improving the quality of care of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 27 publications
3
17
0
1
Order By: Relevance
“…Finally, autopsy was rarely performed in the present cohort because of logistic limitations in our hospital. A number of studies have emphasized that autopsy findings substantially contributed to the diagnosis of critically ill patients [ 39 , 40 ]. Specifically, an autopsic study in patients who died from sepsis has revealed continuous septic foci that may have contributed to multiple organ failure and death [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, autopsy was rarely performed in the present cohort because of logistic limitations in our hospital. A number of studies have emphasized that autopsy findings substantially contributed to the diagnosis of critically ill patients [ 39 , 40 ]. Specifically, an autopsic study in patients who died from sepsis has revealed continuous septic foci that may have contributed to multiple organ failure and death [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies values of 7.5 to 23 %, classified as major, were found in patients admitted to the intensive care unit, with 11-13% for minor discrepancies 5,6 . For patients admitted to general hospitals, there were 6-37 % of major discrepancies and 25-28 % of minor ones 7-9 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the overall rate of MD of tumors varies among different studies, ranging from<4% to 50% of the autopsies performed in patients died either in regular wards and in ICU [8,9,27]; it is arguable that our relatively low rate of MD could be at least partly related to the above-enlisted exclusion criteria which impeded us to know the results of the autopsies performed in other categories of critically ill patients.…”
Section: Our Findings Deserve Some Remarksmentioning
confidence: 99%
“…A number of investigations demonstrated that infections and cardio-respiratory diseases, including pulmonary embolisms and myocardial infarctions account for a substantial rate of MD in this population, with variable effects on the outcome ranging from negligible to substantially deadly [1,[4][5][6][7]. Although the occurrence of autopsy-discovered malignancies is less common [8], yet they can represent as many as 10% of cases [9,10] in patients admitted for reasons other than tumors. However, independently from their rate of occurrence, the ante-mortem diagnosis of neoplastic diseases in critically ill patients appears relevant for two opposite reasons.…”
Section: Introductionmentioning
confidence: 99%